Reported Accommodations and Supports Provided to Secondary and Postsecondary Students With Disabilities: National Perspective. (December 2015) - Newman, Lynn A.; Madaus, Joseph W.
There is a dearth of information on specific accommodations used by students with disabilities at the secondary and postsecondary levels. Using data from the National Longitudinal Transition Study–2, researchers examined a nationally representative cohort of 3, 190 students with disabilities who reported that they had ever enrolled in a postsecondary program since leaving high school. Analysis of differences in rates of self-disclosure indicated that only 35% of youth with disabilities informed their college of their disability. Whereas 95% received disability-based accommodations at the secondary level, only 23% did so at the postsecondary level. Likewise, 59% received at least one modification at the secondary level but only 4% did in college. Implications for practice and future research are discussed.